2021
DOI: 10.1149/1945-7111/ac1d7a
|View full text |Cite
|
Sign up to set email alerts
|

Operando Measurements of Electrolyte Li-ion Concentration during fast charging with FTIR/ATR

Abstract: The ability to charge a Li-ion battery at high charging rates is critical for electric vehicle adoption; however, further study of ion transport is required to develop electrolytes suitable for fast charge. Fourier transform infrared spectroscopy (FTIR) used with attenuated total reflection (ATR) enables operando measurements of liquid electrolytes. This research focused on solvation shifting of solvent infrared absorption bands in the presence of lithium ions. Lithium-shifted infrared absorption bands and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Infrared spectra can thus constitute a ngerprint for some of the components of electrolytes, the SEI and organic electrode materials. Operando measurements would therefore enable the investigation of not only the evolution of the cation solvation structure in the electrolyte 117,118 but also the redox mechanisms and/or degradation processes for organic electrodes. 119 Unfortunately, the study of the formation of the SEI and related passivation layers is limited by the fact that they are commonly very thin (between 5 and a few tens of nm) and consist of compounds containing functional groups similar to those present in the electrolyte they originate from, which is present inside the cell.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…Infrared spectra can thus constitute a ngerprint for some of the components of electrolytes, the SEI and organic electrode materials. Operando measurements would therefore enable the investigation of not only the evolution of the cation solvation structure in the electrolyte 117,118 but also the redox mechanisms and/or degradation processes for organic electrodes. 119 Unfortunately, the study of the formation of the SEI and related passivation layers is limited by the fact that they are commonly very thin (between 5 and a few tens of nm) and consist of compounds containing functional groups similar to those present in the electrolyte they originate from, which is present inside the cell.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…A recent study focused on solvation shifting of solvent infrared absorption bands in the presence of lithium ions, comparing lithium-shifted and non-shifted bands of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) to infer changes in ion concentration during cycling. 140 Lithium concentrations were calibrated using EC/EMC/LiPF 6 electrolytes with known concentrations. A Li-ion half-cell with a graphite anode and EC/ EMC/LiPF 6 electrolyte was examined using FTIR/ATR.…”
Section: Spectroscopy Techniquesmentioning
confidence: 99%
“…Understanding the solvation structure and interfacial transport kinetics of electrolyte is another key step to realize fast-charging of LIBs. Santhanagopalan et al [91] found that Fourier transform infrared spectroscopy (FTIR) combined with attenuated total reflection (ATR) enables operational measurements of liquid electrolyte. At higher charging rates, an increase in local Li + consumption and accumulation due to insufficient ion transport is observed.…”
Section: Theoretical and Experimental Research Techniquesmentioning
confidence: 99%